Existence and multiplicity of solutions for Schrödinger equation with inverse square potential and Hardy–Sobolev critical exponent. (April 2019) - Wang, Cong; Shang, Yan-Ying
Abstract: In this paper, we study a Schrödinger equation involving Hardy–Sobolev critical exponent in R N, the existence of a ground state solution and multiplicity of solutions are established. Our method relies upon Ekeland's variational principle, Nehari manifold and Mountain Pass Theorem.